Left retroperitoneal versus midline transperitoneal approach for abdominal aortic aneurysms (AAAs) repair - Laohapensang K. (2014)
Objective: The purpose of this prospective randomized study was to compare the left retroperitoneal approach (RPA) with the midline transperitoneal approach (TPA) for infrarenal abdominal aortic aneurysms (AAAs) repair with operative details, postoperative complications, and total cost comparision. Material and Method: Between January 2000 and December 2003,36 patients undergoing elective surgery for infrarenal AAAs were included in the prospective comparison of transperitoneal approach (TPA) with retroperitoneal approach (RPA). Thirty-six patients were analyzed, with 18 in group 2 (TPA) and 18 in group I (PRA). There was no significant differences between the groups in patient demographics. (p value > 0.05) Results: There was no significant differences in the aortic cross clamp time, operative time, estimated blood loss and intraoperative blood transfusion between the two groups (p value > 0.05); however, significantly more intraoperative fluid needs and bowel function onset had a statistically longer return in group II (TPA) than in group I (RPA). Statistically reduction in postoperative ileus (> 4 days) and total length of hospital stay was observed in group I (RPA) (p value < 0.05). Postoperative cardiopulmonary complications were statistically significantly more increased in group II (TPA) than in group I (RPA). Wound complications were more in group I (RPA) (1 hematoma, 4 abdominal wall hernia, and 4 chronic wound pain) than in group II (TPA) (2 chronic wound pain). Total cost payment was not significantly different in both groups. Conclusion: The left retroperitoneal approach for infrarenal AAAs repair, with fewer cardiopulmonary complications and shorter hospital stay has more unsatisfactory postoperative wound complications than the midline transperitoneal approach.